Reformulation of Food Security Law to Realize the Welfare State - Syahyu, Yulianto (International Journal of Law Reconstruction, 2025)
The concept of food security is food availability to everyone, which is reflected in the availability of sufficient and productive food in a sustainable manner. The purpose of this study is the reformulation of food security in the framework of people's welfare and national economic recovery with the end result to be achieved from food security to food sovereignty. The method used is juridical normative by examining the sources of law through theories, concepts, and legislation related to research. The results showed there are currently quite a lot regulations of food-related but its implementation is still considered less effective. Strategic steps regarding the reformulation of food security in the framework of national economic recovery for the future can be done by harmonizing and synchronizing legislation related to food, land management and spatial planning, and implementing agrarian reform. Law No. 18 of 2012 which specifically regulates food is considered not in accordance with the needs of the community and the times so that the government is expected to quickly and seriously revise these rules and create new legal rules that can accommodate problems in the community so that in the future not only food security is fulfilled but also food sovereignty.